STRATEGI KEBERLANJUTAN AGRIBISNIS BERAS ORGANIK - Humaidi, Edy; Asriani, Putri Suci; Priyono, Basuki Sigit (Jurnal AGRISEP, 2021)
The purpose of this study is to identify internal factors and external factors of sustainability of organic rice agribusiness, formulate alternative strategies for the sustainability of organic rice agribusiness, analyze the best strategies that can be applied in the sustainability of organic rice agribusiness. The study used Primary and Secondary Data Types. Primary Data Collection Techniques were obtained through Interviews/Questionnaires with respondents and farmer experts. The analysis technique used is the IFE and EFE matrix, to obtain an alternative strategy using SWOT, while to choose the best strategy use QSPM. The results of this study are: 1. Identification of internal factors shows that there are 23 strengths and 9 weaknesses that have been held in the sustainability of organic rice agribusiness in the Handayani farmer group. 2. From the strategic focus, four alternative strategies are obtained, namely organic rice through the optimal use of production inputs and skills owned by farmers to meet market prospects and increase demand, develop and expand the organic rice market out of the South Sumatra region through the application of internet and work technology together with the government and partners, optimizing the quality of organic rice Through proper handling and postharvest handling, and making Suka Makmur Village an organic agrotourism village. 3. The QSP matrix results show the best strategy of the four alternative S-O strategies is to optimize the quality of organic rice through proper handling and postharvest handling, this condition is seen from the Total Total Attractive Score (TAS) of 4.5406.